Characterization and challenges of vacant urban land in cities of the Greater Santa Fe Agglomeration (Argentina) (Revista Iberoamericana de Estudios Municipales, 2025)
Vacant urban land is associated with the expansion of urban areas, the increase in lot prices, and other factors. Through documentary analysis and interviews with political officials and members of technical teams, the research characterizes the situation of this type of land in the cities of the Greater Santa Fe Agglomeration in terms of the number of vacant urban lots, the instruments available to local governments to mobilize it and the challenges in managing it. The findings indicate that the issue is not a priority on government agendas. The only regulatory tool that penalizes its possession is a real estate surcharge, which, being generally low, does not incentivize mobilization. Enforcement procedures are sporadic, and local governments do not create land reserves with lots to deed.
Keywords: Urban vacant land; urban growth; mobilization instruments; local States; Greater Santa Fe Agglomerate